In the name of good - Nogueira, Roberto Círio (Opiniães, 2010)
Essay focused on the war started by Zé Bebelo in Grandesertão: veredas, whose cause is founded on an idealizedcomprehension of modernity. According to thisconception, the redemption of the sertanejos’ miserablecondition would only be possible if a revolutionary actioncould supplant the jagunços’ power through republicanorder. The reverse of this social-political view fi ndsin Rubem Fonseca’s short stories “Intestino grosso”and “O Cobrador” some examples of demystifi cationof a utopian modernity and of a violent strategy ofsocial inclusion in the universe of consumption. Suchcontraposition reiterates a perception of a future that isno longer how it used to be.